(3fXQjGJ hSjGSGJs - (3Ydj YHO GdaJGM(B, (3CHhTQGQs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B,s, 2007)
(3CgejI GdGbJUGO GdOhdj,fXQjGJ GdJLGQI GdOhdjI, GdfXQjI GdMOjKI ddJLGQI GdOhdjI, efMfi GdYQV heYOd GdJHGOd GdJLGQj, fXQjI gjcTQ(B-(3Chdjf ,GdGNJHGQ GdJLQjHj dfXQjJj GdJcGdja GdfSHjI hgjcTQ(B-(3Chdjf, Gdfeh GdGbJUGOj hGdJLGQI GdOhdjI, JMQcGJ YhGed GdGfJGL GdOhdjI, GdEbQGV GdOhdj hCReI GdOjhf GdYGdejI, GdSjGSGJ GdJLGQjI,BKGQ GdSjGSGJ GdJLGQjI, GdbjhO GdJLGQjI aj hVY GdJhGRf GdLRFj, MGdI GdOhdI GdcHjQI, CfhGY GdSjGSGJ GdJLGQjI, GdSjGSGJ GdESJQGJjLjI GdJLGQjI, GdJcGed GdGbJUGOj, GdefXeGJ GdGbJUGOjI GdJGHYI GdCee GdeJMOI(B.s
(3GdWHYI GdLOjOI SfI (B2015(3;HHdjhZQGajG(B:(3U(B.521-525 (3GdghGeT(B:(3U(B.517-520s
Keywords: (3GdEbJUGO Ohdjs